Early Identification of Exacerbations in Patients With Chronic Obstructive Pulmonary Disease - Barbara P. Yawn (SAGE Publishing, 2013)
Frequent exacerbations of chronic obstructive pulmonary disease (COPD) place a considerable burden on the health care system and are a major cause of decreased health-related quality of life, accelerated pulmonary decline, and mortality in individual patients. Primary care physicians are usually the first point of contact for patients experiencing an exacerbation and are therefore best placed to prevent, identify, and treat these events in a timely manner. This review addresses the triggers and risk factors for COPD exacerbations, including the exacerbation-prone phenotype. The prevention, prompt diagnosis, and early appropriate pharmacological/nonpharmacological treatment of COPD exacerbations is important, as early recognition of symptoms (as supported by tools for measuring the illness/wellness experience of COPD patients in primary care) and treatment lead to optimal recovery in these patients. The review also highlights the importance of the urgency in identifying exacerbations and the important role played by primary care physicians in the prevention and postexacerbation management of patients with COPD.